2020
DOI: 10.1002/ajhb.23513
|View full text |Cite
|
Sign up to set email alerts
|

Field methods and strategies for assessing female reproductive functioning

Abstract: A detailed understanding of female reproductive functioning is important to many disciplines including anthropology, evolutionary theory, demography, psychology, and biomedicine. In this article, I describe strategies and methods that have been used successfully in community‐based studies of human reproduction, many in remote locales, to produce high quality biomarker data. These techniques are applicable to a wide range of research questions and populations, and to persons from adolescence through senescence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 200 publications
(244 reference statements)
0
17
0
Order By: Relevance
“…Interileukin‐10 is also measurable from saliva but has been shown to be susceptible to variation in acute stress (Szabo et al, 2016), so may be of minimal use as a biomarker of autoimmunity. Further, reproductive hormones can be measured in saliva (Kozloski et al, 2014; Trumble et al, 2013; Vitzthum, 2020) and can be analyzed in conjunction with other biomarkers of autoimmunity to test sex‐related hypotheses associated with AIID. In general, saliva is non‐invasive, easy to collect, and inexpensive (Javaid et al, 2016), so population‐based research on AIID could consider targeting these kinds of biomarkers.…”
Section: What Methods Have Been Used To Measure Autoimmunity In Populmentioning
confidence: 99%
See 1 more Smart Citation
“…Interileukin‐10 is also measurable from saliva but has been shown to be susceptible to variation in acute stress (Szabo et al, 2016), so may be of minimal use as a biomarker of autoimmunity. Further, reproductive hormones can be measured in saliva (Kozloski et al, 2014; Trumble et al, 2013; Vitzthum, 2020) and can be analyzed in conjunction with other biomarkers of autoimmunity to test sex‐related hypotheses associated with AIID. In general, saliva is non‐invasive, easy to collect, and inexpensive (Javaid et al, 2016), so population‐based research on AIID could consider targeting these kinds of biomarkers.…”
Section: What Methods Have Been Used To Measure Autoimmunity In Populmentioning
confidence: 99%
“…In the last decade, biomarker analysis from field‐friendly (i.e., affordable; minimally‐invasively collected; easily‐stored) samples has come into focus within the fields of human biology and related disciplines (Eick et al, 2019; Eick et al, 2020, 2020; Goldman et al, 2017; Hoke, McCabe, Miller, & McDade, 2018; Ice & James, 2007; McDade, 2014; McDade, Williams, & Snodgrass, 2007; Mei, Alexander, Adam, & Hannon, 2001; Valeggia, 2007; Vitzthum, 2020). This shift in focus has opened doors for population‐based research (i.e., interdisciplinary, multi‐method human health research focused on specific groups of individuals) because in many cases, venous blood draw, magnetic resonance imaging, tissue sampling, and other more invasive, specialized, or expensive methods for assessing health‐ and physiology‐related metrics are difficult or impossible in non‐clinical settings (McDade et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The delay is attributable, in part, to the technological and logistical challenges of investigating the reproductive physiology of populations in remote locales (Leslie & Little, 2003; Vitzthum, 2021). Furthermore, in the natural fertility populations in which anthropologists typically work, a large segment of the fecund women of reproductive age are either pregnant or breastfeeding, and thus not experiencing menstrual cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Cycle length (duration in days) is the most studied feature of the menstrual cycle. Bookended by the first day of menstrual bleeding, menses can be recorded on a calendar or other device and the days counted (Vitzthum, 2021). Several studies (Creinin et al, 2004; Jukic et al, 2008) have reported various biases in recalled cycle length and variability (also referred to as predictability or regularity) including a preference for reporting 28 or 30 day lengths, which would tend to give the impression of less cycle variability than actually exists.…”
Section: Introductionmentioning
confidence: 99%
“…women's reproductive span has an impact on wom-nen's reproductive decisions inclduing when to get pregnant, spacing between pregnancies, and finally when to have the last birth. The span also influences the fertility levels in the population [4].…”
Section: Introductionmentioning
confidence: 99%